The Interactive Role of Human and Environmental Dimensions inl the Desertification Debate - Smith, Mark Stafford; Reynolds, James F (Annals of Arid Zone, 2016)
We summarize a new synthetic framework for understanding and responding. to desertification that emerged from the 88th Dahlem workshop on "An Integrated Assessment of the Ecological, Meteorological and Human Dimensions of Global Desertification". We refer to this framework as the Dahlem Desertification Paradigm. This paper then examines one thread through this framework - the chain of logic that runs from the assertion that simultaneous consideration of both the human and environmental aspects of desertification if critical for any advances on dealing with desertification and degradation at all scales; that the coupled human and environmental parts or the system change over time;' in ways that may be more or less dysfunctional; to emphasize the critical importance of assisting the rate of development of appropriate local environmental knowledge (LEK) in minimizing dysfunction. Given the increasing rates of change being imposed on our worlds, and the particular difficulties in developing experiential knowledge quickly in variable arid environments, we conclude that support for better integration of LEK with the scientific method is one critical pillar in creating a learning society in dry lands